Development and application of a lateral flow colloidal gold immunoassay strip for the rapid quantification of ciprofloxacin in animal muscle. Issue 25 (13th June 2019) - Yu, Lu; Liu, Minxuan; Wang, Tianying; Wang, Xianghong
Abstract : Ciprofloxacin is a major metabolite of enrofloxacin. Abstract : Ciprofloxacin is a major metabolite of enrofloxacin. It has a long metabolic cycle, but is often neglected. The detection of residual ciprofloxacin in food can reflect the amount of enrofloxacin to some extent. A method for quantitative detection of ciprofloxacin by a colloidal gold lateral flow immunoassay was developed. The colloidal gold as a labeling material was characterized using a transmission electron microscope and a dynamic light scattering analyzer. The detection time and pretreatment method were optimized. The signal intensity of the test strip test line and control line was measured using a colloidal gold test strip reader. The T / C ratios of PBS and positive samples were defined as B 0 and B x . The standard curve was established by plotting the B x / B 0 ratio against the concentration of ciprofloxacin. The results showed that the colloidal gold particles are uniform in size and good in quality. The average size of prepared GNP was ( Z -average) 25.09 nm. The detection time was 15 min. Under the optimum conditions, the detection limit of the test strip was 0.75 ng mL −1, and the linear range was 0.78–25 ng mL −1 . The LOD of the initial sample was 7.5 ng g −1 . This method was applied to the determination of ciprofloxacin in spiked fish, beef and shrimp samples, and recoveries ranged from 77.47% to 89.69% with relative standard deviations between 0.89% and 9.12%. Therefore, this method has the advantages of simple operation, good stability and high sensitivity, and can satisfy the quantitative detection of ciprofloxacin in various meat samples. At the same time, this method provided the possibility of monitoring the residues of ciprofloxacin.